MODEL INDUKTIF: SEBUAH TAWARAN DALAM MENGAJARKAN STRUKTUR KALIMAT - Hamdani, Agus (Universitas Pendidikan Indonesia, 2017)
This article contains ideas to present examples of inductive modeling in learning sentence structure. The stagesof the offered inductive model consist of the introductory stage, the data presentation stage, the stage of conceptachievement, the stabilization stage, and the closure stage. Each step consists of several steps that are concretelyillustrated through a learning scenario. The emphasis of this model is directed to the development of students'thinking skills in addition to the complete mastery of the contents of the lecture structure of the sentencepresented. The expected instructional impact through this inductive model scenario example is to improvestudents' ability to master sentence concept and deepen their experience in dealing with sentence structure data.The expected impact of the comrades is to instill the habit of always thinking critically and fostering the spirit ofcreativity.